Education in a Changing World : Flexibility, Skills, and Employability - Wang, Yidan (World Bank, Washington, DC, 2017)
New technologies, globalization, the information revolution, and labor market changes have affected the world economy on an unprecedented scale. As a consequence, the demand for a skilled workforce has increased, world trade and migration have intensified, and the divide between the haves and have-nots has vastly widened. While many developed countries have by now gone through a demographic transition, with declining birth rates and an increase in the aging population, low-income countries in particular will see an upswing in population growth. Between now and 2050, for example, the labor force in Africa is projected to increase by 125 percent; in Latin America, by 26 percent; and in Asia, by 22 percent. At the same time, the labor force in Europe will decline by 23 percent. Given these circumstances, the key policy challenge is to ensure that the emerging workforce in developing countries has the skills needed to escape the cycle of poverty and take advantage of the opportunities made possible by globalization and technological change. This paper puts education under the lens of the changing demands of technology, the labor market, demography, and migration. It identifies the weaknesses in current education systems, such as restricted access, skills mismatches, and weak school-to-work linkages. It calls for making education systems more flexible and responsive to change so that they maximize human resources, equip people with updated skills, and prepare youth for the world of work. It specifically looks at the education status of four types of countries at different stages of development and growth and makes recommendations on priorities and strategies for each group.